Bone mineral density in healthy female adolescents according to age, bone age and pubertal breast stage - Oliveria, Maria Regina Moretto de [UNESP]; Silva, Carla Cristiane da; Kurokawa, Cilmery Suemi; Fortes, Cristina Maria Teixeira; Capela, Renata Campos; Teixeira, Altamir Santos; Dalmas, José Carlos; Goldberg, Tamara Beres Lederer (Bentham Open, 2011)
This study was designed to evaluate bone mineral density (BMD) in healthy female Brazilian adolescents in five groups looking at chronological age, bone age, and pubertal breast stage, and determining BMD behavior for each classification. Seventy-two healthy female adolescents aged between 10 to 20 incomplete years were divided into five groups and evaluated for calcium intake, weight, height, body mass index (BMI), pubertal breast stage, bone age, and BMD. Bone mass was measured by bone densitometry (DXA) in lumbar spine and proximal femur regions, and the total body. BMI was estimated by Quetelet index. Breast development was assessed by Tanner's criteria and skeletal maturity by bone age. BMD comparison according to chronologic and bone age, and breast development were analyzed by Anova, with Scheffe's test used to find significant differences between groups at P≤0.05. BMD (g·cm(-2)) increased in all studied regions as age advanced, indicating differences from the ages of 13 to 14 years. This group differed to the 10 and 11 to 12 years old groups for lumbar spine BMD (0.865±0.127 vs 0.672±0.082 and 0.689±0.083, respectively) and in girls at pubertal development stage B3, lumbar spine BMD differed from B5 (0.709±0.073 vs 0.936±0.130) and whole body BMD differed from B4 and B5 (0.867±0.056 vs 0.977±0.086 and 1.040±0.080, respectively). Bone mineralization increased in the B3 breast maturity group, and the critical years for bone mass acquisition were between 13 and 14 years of age for all sites evaluated by densitometry.
Keywords: Adolescents; Bone mineral density; Breast development; Female; Pubertal events